2008
DOI: 10.14712/18059694.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Alters Cytoskeletal Integrity and Migration in Colon Cancer Cells

Abstract: Zinc has been shown to have inhibitory effects on proliferation and metabolism of malignant colonocytes. Still, there is no information available concerning putative effects of zinc against motility and migration of colon cancer cells. Using fluorescence microscopy, immunoblotting and microflorimetry we show that treatment with zinc sulfate affected motility, invasiveness, cytoskeletal integrity and expression of selected markers (E-cadherin, catenin, vimentin, tubulin and actin) of invasive SW480 colon tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The morphology of the MC3T3-E1 cells was round on both of the flat substrates (TC, non-patterned PDMS). In the case of motility, cells on TC did not exhibit a dose dependence on zinc, while migration of the MC3T3-E1 cells on flat PDMS was very sensitive to zinc concentration, similar to previous studies on cancer cell migration [ 39 , 40 , 42 ]. This suggests that the mode of migration on PDMS is fundamentally different than on TC for the pre-osteoblasts.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The morphology of the MC3T3-E1 cells was round on both of the flat substrates (TC, non-patterned PDMS). In the case of motility, cells on TC did not exhibit a dose dependence on zinc, while migration of the MC3T3-E1 cells on flat PDMS was very sensitive to zinc concentration, similar to previous studies on cancer cell migration [ 39 , 40 , 42 ]. This suggests that the mode of migration on PDMS is fundamentally different than on TC for the pre-osteoblasts.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, cell migration on flat PDMS was considerably faster (0.27–0.44 µm/min) and showed a steady decrease with increasing zinc concentration ( Figure 5 E). The migratory behavior of MC3T3-E1 cells on flat PDMS is similar to previous reports on breast cancer cells, where the addition of exogenous zinc also attenuated migration [ 39 , 40 ]. Motility of cells on both wide (0.29–0.34 µm/min) and narrow (0.28–0.36 µm/min) PDMS patterns was similar to that on flat PDMS, however zinc concentration did not have a significant effect ( Figure 5 E; p = 0.35–0.86).…”
Section: Resultssupporting
confidence: 87%
“…Zn 2+ is an important regulator of the cytoskeleton in nucleated cells. 39 40 Zn 2+ regulates tubulin polymerization leading to nuclear transport of transcription factors in neuronal cells, 41 and has been shown to regulate the actin cytoskeleton, focal adhesion dynamics and cell migration in PC-3 and HeLa cells, 35 where Zn 2+ chelation supresses filopodia formation and results in the loss of stress fibres. Conversely, treatment with Py increased filopodia formation, supressed stress fibres and decreased the number and size of focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could explain the presence of elevated Zn levels in secondary liver metastases compared with primary colorectal tissues. 21 Moreover, a recent study by Rudolf et al 22 has shown that Zn has the potential to be used in chemoprevention of advanced colorectal carcinoma. Zn may help suppress free radicals through metallothionein synthesis, act as an inhibitor of the nicotinamide adenine dinucleotide phosphate (reduced)-dependent lipid peroxidation, and prevent lipid peroxidation by inhibition of glutathione depletion.…”
Section: Discussionmentioning
confidence: 99%